Frequency of Sexual Dysfunction among Patients Using Cannabis: A Cross-Sectional Study - Fazale Rabbani; Israr ud Din; Waleed Ahmad; Sumaira Mehreen (Journal of Gandhara Medical and Dental Sciences, 2025)
OBJECTIVES